A Polyoxoniobate/g-C3N4 Nanoporous Material with High Adsorption Capacity of Methylene Blue from Aqueous Solution - Gan, Qiuyan; Shi, Weilong; Xing, Yanjun; Hou, Yu (Frontiers in Chemistry, 2018)
A polyoxoniobate/g-C3N4 nanoporous material with functional groups has been synthesized by using carbon nitride (g-C3N4) and hexaniobate (K8Nb6O19·10H2O, abbreviated as NbO) as precursors. The structure and compositions of the as-prepared nanomaterials were characterized by XRD, FT-IR, FESEM, TEM, and XPS. These two kinds of materials interact with each other forming a hybrid composite, which can be used as an adsorbent for removing a cationic dye (methylene blue, MB) from wastewater with excellent adsorption capacity. Furthermore, parameters that can affect adsorption process including initial dye concentration, pH and temperature were investigated by bath adsorption experiments. The results indicated that the maximum adsorption capacity of NbO/g-C3N4 can reach up to 373.1 mg g−1. Moreover, the equilibrium experiment data fitted Langmuir isotherm well and the adsorption kinetics showed that the pseudo second order model can satisfyingly described MB adsorption kinetics. The thermodynamic analysis indicated that the adsorption was endothermic and spontaneous.